Modification by light of nitrite release and accumulation by Neurospora crassa - H. NINNEMANN (Fungal Genetics Reports, 1990)
Activity of nitrate reductase (NR) induced by nitrate in the growth medium can be tested by diazotation of the nitrite formed during an activity test (Snell and Snell, 1949, Colorimetric Methods of Analysis, pp. 802-807). Pink instead of colorless controls (NADPH omitted) in these tests indicated nitrite present in the samples without NR activity and caused us to assay for nitrite excreted into the culture medium and for nitrite accumulated in the mycelia of Neurospora crassa strain al-2;bd.